Temperature and reaction atmosphere effects on the properties of corn stover biochar. Issue 3 (1st November 2016) - Brewer, Catherine E.; Hall, Eric T.; Schmidt‐Rohr, Klaus; Laird, David A.; Brown, Robert C.; Zygourakis, Kyriacos
Abstract : Biochar properties can vary widely depending on feedstock and processing conditions, which can make meaningful comparisons between biochars difficult. Clear trends can be observed in slow pyrolysis biochar properties over a 300–800°C range of highest treatment temperatures (HTT). These trends, however, are much less consistent for biochars made under slightly oxidizing conditions, such as in gasification and internally‐heated kiln carbonization processes. In this study, slow pyrolysis biochars were produced from corn stover under either pure nitrogen or nitrogen + 5% oxygen atmospheres over a 200–800°C HTT range. For the biochars made at 300 and 400°C, the presence of oxygen in the reaction environment resulted in biochars with properties similar to those of biochars produced at higher HTTs in pure nitrogen. Addition of oxygen has only minor effects on biochar bulk oxygen content or abundance of surface oxygenated functionalities. Thermogravimetric analysis with mass spectroscopy (TGA‐MS) indicated that the apparent increase in HTT for chars made in the O2 environment at 300 and 400°C resulted in the removal of methyl and higher alkyl functionalities in the biomass feedstock. Advanced solid state 13 C nuclear magnetic resonance spectroscopy (NMR) methods to quantify carbon functional group abundance and aromaticity supported this observation. Overall, addition of oxygen to the pyrolysis atmosphere will increase pyrolysis process severity but will not create oxygenated groups on biochar surfaces as biochar aging does. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 696–707, 2017